Frequency shifts of surface plasmon resonances in calculating the absorption coefficient of a composite based on bimetallic 1D-systems - Koval, A.O. (Physics and Chemistry of Solid State, 2023)
In this paper analyzes the electromagnetic radiation absorption by a composite based on bimetallic nanowires. Using the Drude-Lorentz theory it was obtained the relationship for the polarizability frequency dependences, as well as real and imaginary parts of the dielectric function of layered 1D-systems was obtained. It is shown that the structure in the form of a metal core covered with a layer of another metal leads to splitting and the appearance of two maxima in the frequency dependence of the absorption coefficient. The magnitude and position of the maxima are determined by the composition of bimetallic nanowires and the volume content of metals. The influence of the dimensionality of the systems has been established by comparing the frequency dependences of the composite absorption coefficient based on bimetallic nanowires and nanoparticles. Calculations were performed for Ag@Au and Au@Ag nanowires immersed in Teflon.